Determinan Dana Pihak Ketiga Bank Syariah di Indonesia: Model Vector Autoregresive - Darwis Harahap (Ekonomi Syariah IAIN Kudus, 2017)
One of the performance indicators in Islamic banking industry is a third party fund. This study aims to analyze the determinant factors of the third party funds in the Indonesian Islamic banking industry. The method that used in this study is vector auto regressive (VAR). The variables in this study are capital adequacy ratio (CAR), non-performing financing (NPF), and financial to deposit ratio (FDR) as a benchmark of the financial performance of Islamic banking. The results of causality test results shows that the CAR does not affect LDPK, while LDPK affects CAR. NPF relationship with LDPK equally doesnt had an affects. Co-integration Test Results do not find co-integration equation, so there is no long-term relationship between the variables LDPK, CAR, NPF and FDR. Relationships occur only in the short term. The result of Vector Auto Regressive (VAR) test of impulse response function (IRF), variable shock causes disturbance variable itself and other variables in different variations. Salah satu indikator kinerja dari industri perbankan syariah ialah dana pihak ketiga. Penelitian ini bertujuan untuk melihat faktor yang memengaruhi dana pihak ketiga pada industri perbankan syariah di Indonesia. Penelitian ini menggunakan metode vector auto regressive (VAR). Variabel yang dipergunakan ialah rasio kecukupan modal (CAR), tingkat pembiayaan bermasalah (NPF), dan tingkat likuiditas (FDR) sebagai acuan kinerja keuangan dari industri perbankan syariah. Hasil uji kausalitas menunjukkan bahwa CAR tidak mempengaruhi LDPK. Sementara LDPK mempengaruhi CAR. Hubungan NPF dengan LDPK sama-sama tidak mempengaruhi. Hasil Uji Kointegrasi tidak ditemukan persamaan kointegrasi maka tidak terdapat hubungan jangka panjang antara variabel LDPK, CAR, NPF dan FDR. Hubungan yang terjadi hanya dalam jangka pendek. Hasil Analisis Vector Auto Regessive (VAR) dengan Analisis impulse response function (IRF) goncangan variabel menyebabkan ganguan variabel itu sendiri dan variabel lain dalam berbagai variasi.